HIBAH PERSPEKTIF FIKIH, KHI DAN KHES - Zakiyatul Ulya (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2018)
Both fikih, KHI and KHES have their respective concepts of hibah, although it can not be denied that fikih is made the earliest reference by others. In this case, the concept of grant is described in more detail in fikih and KHES than in KHI. Whereas when compared, all three have similarities and differences. In terms of understanding, the three equally interpret the hibah as a gift of property to others without reward. In terms of rukun, both KHI and KHES closer to the opinion of jumhur ulama, with additional witness in KHI and qabd in KHES. In terms of syarat, there are restrictions on the age of the grantor in KHI and KHES. In addition, KHES also justifies iqrar in writing, gestures or actions other than speech. In terms of hibah revocation, all three share similar conditions that allow and prohibit it. On the other hand, fikih explains the legal basis of the hibah and the lesson, KHI describes the implementation of hibah of WNI and KHES explains several ways of hibah.